2016
DOI: 10.15406/jdhodt.2016.05.00150
|View full text |Cite
|
Sign up to set email alerts
|

Primary Health Center Approach for Oral Health Related Knowledge, Attitude and Practice among Primary Health Care Workers of Western India

Abstract: Background: Health care workers form an important component of the health care system of any nation, they should have adequate knowledge about oral health as it directly affect the general health, of the people this study was carried out to assess knowledge, attitude, and practices among primary health care workers in Jaipur. Materials & methods:This cross-sectional study was conducted among 220 Primary Health care workers present on the day of the survey. Among 220 samples 130 & 90 health workers were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
1
6
0
1
Order By: Relevance
“…A study conducted by Sandhya et al [7] showed that most of the respondents knew the importance of daily oral hygiene measures that help in preventing dental diseases. In contrast, Yadav et al [12] reported adequate awareness of the active role of sugar in dental decay but poor oral hygiene practices. About one-third of the participants were unaware of the capability of uoride products in caries prevention, while the literature search reveals a mixed outcome on the knowledge scores.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…A study conducted by Sandhya et al [7] showed that most of the respondents knew the importance of daily oral hygiene measures that help in preventing dental diseases. In contrast, Yadav et al [12] reported adequate awareness of the active role of sugar in dental decay but poor oral hygiene practices. About one-third of the participants were unaware of the capability of uoride products in caries prevention, while the literature search reveals a mixed outcome on the knowledge scores.…”
Section: Discussionmentioning
confidence: 94%
“…[9,13] It was seen that the majority of the participants depend on health education programs as the source of knowledge, while awareness programs in mass media were reported as the primary source in other similar studies. [12,13,20] Despite having a profound effect in daily life, social media remains ineffective for the dissemination of oral health knowledge, especially in rural areas. Lack of oral health education, inadequate motivation, and insu cient allocation of resources by the local health administrative system might be the cause for lack of knowledge among CHWs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations